Application Of Ethnography Method In Conservation Area Efforts By Salam, The Conservation And Social Community Empowerment Organization - Oktiyas Muzaky Luthfi; Mayang Setianingsih (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
SALAM is not profit organization that active on community empowerment especially on the coastal community in the south of Malang district that was Kondang Merak. The strong and rational reason to be community agent in this location because Kondang Merak area has typical of the tropical ecosystem such as mangrove, seagrass and coral reef where these potential assets used unsustainable manner by the community. SALAM used ethnography method for developing the strategy to empowerment the community. This method is unique where an agent should follow the daily activity of community in long-term, seen and heard what the community said and asked and collected data with persuasive way. Through this method, SALAM has succeeded to change the mindset of actors in the community from destroyers to be the conservationist and nature-minded.